Vieussens’ arterial ring: a rare coronary variant anatomy - Doğan, Nurullah (Diagn Interv Radiol, 2019)
PURPOSE: We aimed to evaluate Vieussens’ arterial ring (VAR) variants by consecutive coronary computed tomography (CT) angiography examinations. METHODS: We retrospectively evaluated the presence of VAR in a total of 3443 consecutive coronary CT angiography examinations performed between November 2010 and January 2015. CT examinations were performed with a 64-row multidetector computed tomography (MDCT) scanner. All CT angiography images were evaluated for the presence and morphologic features of VAR subtypes. VAR variants were classified into four subgroups. RESULTS: Eleven VAR variations (3.19‰) were identified. Type 1A was the most common VAR type (n=8), followed by Type 2 (n=2) and Type 3 (n=1). Type 1B was not detected. CONCLUSION: Although VAR variation is less frequently detected with coronary CT angiography than in previously reported anatomic series, coronary CT angiography is quite effective to reveal VAR subtypes and other relevant cardiocoronary anomalies.